Analisis Hukum Persaingan Tidak Sehat dalam Praktik Bisnis di Indonesia; Perspektif Hukum Islam - Ratna Dewi; Gagah Satria; Aruman Aruman; Jeklira Tampubolon; Erlan Basuki; Umbu Landu Parangga (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze the regulation and enforcement of unfair business competition law in Indonesia and to examine its conformity with the principles of Islamic law. The research employs a normative legal method using statutory and conceptual approaches, involving an analysis of Law No. 5 of 1999, relevant legal literature, and Islamic legal sources. The findings indicate that Indonesian positive law and Islamic law share substantial alignment in prohibiting market manipulation and economic exploitation. Moreover, Islamic law provides a more comprehensive ethical foundation through the prohibition of ihtikar, tadlis, and najasy, emphasizing moral and ethical values in economic activities. Therefore, the integration of Islamic business ethics can serve as a moral complement to positive legal regulations and enhance the effectiveness of competition law enforcement, contributing to the creation of a fair, transparent, and socially just business environment.